ATTITUDE TO ORGAN DONATION AND AUTOPSY IN DIFFERENT RELIGIOUS DENOMINATIONS (Journal of Forensic Medicine & Toxicology, 2015)
Organ transplantation is at the forefront of health care today. It can potentially change the very nature of human life, should it become available and affordable to the masses. Apart from the high infrastructure cost such procedures demand, the scarcity of organs that can be retrieved adds to the cost. Apart from popularising the concept of organ donation, the elitist image of such procedures should be shed in order to attract more donors. A careful target oriented approach to mobilize donors in significant numbers is needed in the field of organ location and harvesting, to eventually make this advance available to the average citizen. Any effort at persuading people to donate organs must be sensitive to their religious and cultural beliefs. The perception of life and death varies from religion to religion. Certain customs are unique to each religion. Awareness about these beliefs and attitudes towards autopsy and organ donation will make a salutary difference to efforts aimed at locating potential organ donors. In this article a brief overview of religious beliefs and attitudes towards autopsy and organ donation has been presented.
Keywords: religion; donation; transplantation